Антикорупційна практика в Україні під впливом війни - Мітіна, Марія Максимівна; Логінова, Марина Вікторівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Ukraine is plagued by corruption, and the consequences of the war have had a profound impact on anti-corruption practices. This study delves into the complex relationship between conflict and corruption, examining how wartime conditions have shaped Ukraine’s approach to fighting corruption. By examining the challenges and successes of anti-corruption initiatives in the context of conflict, this analysis examines the legal reforms developed in response to the war. By examining the dynamics of war and corruption, this study will shed light on the nuanced evolution of anti-corruption practices in Ukraine, offering insights that are crucial to understanding the broader implications of the fight against corruption in conflict-affected region